Maturation of the Human Immunoglobulin Heavy Chain Repertoire With Age - Ghraichy, Marie; Galson, Jacob D.; Kovaltsuk, Aleksandr; von Niederhäusern, Valentin; Pachlopnik Schmid, Jana; Recher, Mike; Jauch, Annaïse J.; Miho, Enkelejda; Kelly, Dominic F.; Deane, Charlotte M.; Trück, Johannes (Frontiers in Immunology, 2020)
B cells play a central role in adaptive immune processes, mainly through the production of antibodies. The maturation of the B cell system with age is poorly studied. We extensively investigated age-related alterations of naïve and antigen-experienced immunoglobulin heavy chain (IgH) repertoires. The most significant changes were observed in the first 10 years of life, and were characterized by altered immunoglobulin gene usage and an increased frequency of mutated antibodies structurally diverging from their germline precursors. Older age was associated with an increased usage of downstream IgH constant region genes and fewer antibodies with self-reactive properties. As mutations accumulated with age, the frequency of germline-encoded self-reactive antibodies decreased, indicating a possible beneficial role of self-reactive B cells in the developing immune system. Our results suggest a continuous process of change through childhood across a broad range of parameters characterizing IgH repertoires and stress the importance of using well-selected, age-appropriate controls in IgH studies.